Introduction and integration of PrEP and sexual and reproductive health services for young people: Health provider perspectives from South Africa - Pleaner, Melanie; Scorgie, Fiona; Martin, Catherine; Butler, Vusile; Muhwava, Lorrein; Mojapele, Maserame; Mullick, Saiqa (Frontiers in Reproductive Health, 2023)
South Africa has one of the largest HIV epidemics in the world, with particularly high prevalence among adolescent girls and young women (AGYW). Oral PrEP was introduced in the public sector in 2016 in a phased manner. Given the important role played by health providers, research was undertaken to understand their experiences of and attitudes towards introduction of PrEP as a new HIV prevention method, and its integration within broader sexual and reproductive health (SRH) services for youth. A survey was undertaken with 48 purposively sampled health providers working in primary health care facilities and mobile clinics in three provinces in South Africa. Qualitative analysis was performed on free-text responses to open-ended questions in the survey, using an inductive approach to code the data in NVivo v.12 software. Health providers expressed concerns about adding a new service to an already overburdened health system, and worried that young people seeking PrEP would divert staff from other critical services. While most recognised the benefits and opportunities afforded by HIV and SRH service integration, providers highlighted the extra time and resources such integration would require. Many were anxious that PrEP would encourage disinhibition and increase unprotected sex among AGYW, and held judgemental attitudes about young people, seen as largely incapable of taking responsibility for their health. Findings underscore the importance of consulting health providers about implementation design and providing channels for them to express their misgivings and concerns, and training needs to be designed to address provider attitudes and values. Opportunities need to be sought to strengthen the provision of adolescent and youth friendly services – including adolescent-health provider dialogues. Insights from this study can assist in guiding the introduction of new HIV prevention methods into the future.